2017
DOI: 10.1007/s00277-017-3061-3
|View full text |Cite
|
Sign up to set email alerts
|

Ibrutinib versus previous standard of care: an adjusted comparison in patients with relapsed/refractory chronic lymphocytic leukaemia

Abstract: This study explored the relative efficacy of ibrutinib versus previous standard-of-care treatments in relapsed/refractory patients with chronic lymphocytic leukaemia (CLL), using multivariate regression modelling to adjust for baseline prognostic factors. Individual patient data were collected from an observational Stockholm cohort of consecutive patients (n = 144) diagnosed with CLL between 2002 and 2013 who had received at least second-line treatment. Data were compared with results of the RESONATE clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…Other published analyses support the current findings, showing the clinical benefits of ibrutinib outside of RCTs [31]. Using similar methodology to the current study, PLD were collected from an observational cohort of R/R patients ( n = 144) diagnosed with CLL between 2002 and 2013 in Sweden, and the ibrutinib arm of RESONATE™.…”
Section: Discussionsupporting
confidence: 76%
“…Other published analyses support the current findings, showing the clinical benefits of ibrutinib outside of RCTs [31]. Using similar methodology to the current study, PLD were collected from an observational cohort of R/R patients ( n = 144) diagnosed with CLL between 2002 and 2013 in Sweden, and the ibrutinib arm of RESONATE™.…”
Section: Discussionsupporting
confidence: 76%
“…More recently, Quick, by using the Research Collaboratory for Structural Bioinformatics (RCSB) protein data bank, has identified several anticancer drugs that interact with BPAG1, MACF1, and plectin [ 143 ]. Ibrutinib is one common ligand for both BPAG1 and MACF1, and is used clinically for the treatment of lymphoma and leukemia [ 144 , 145 ]. PP121, showing antitumorigenic effects on esophageal cancer and anaplastic thyroid carcinoma by perturbing PI3K and mammalian target of rapamycin (mTOR) kinase activities [ 146 , 147 ], is identified as an MACF1 ligand.…”
Section: Mammalian Plakins In Human Cancermentioning
confidence: 99%
“…In another analysis including R/R CLL in second and subsequent lines of treatment, 29 an OS advantage was noted when comparing ibrutinib (with or without BR) and BR alone. 30 In other studies arriving at the same conclusion, 31 , 32 chemotherapy +/− anti CD20 regimens used in a real-world setting were compared with ibrutinib data of the clinical trials Resonate and Helios. However, there is now evidence that adherence to treatment with ibrutinib in the real-world population did not reflect the data obtained in clinical trials, 22 , 33 possibly due to the heterogeneity of the patient populations or to a more limited experience of physicians in managing side effects occurring on treatment.…”
Section: Discussionmentioning
confidence: 99%